KECERDASAN NUMERIK DAN SPASIAL TERHADAP KEMAMPUAN MATEMATIS SISWA - Selviana Nabilah Aziz; Indra Martha Rusmana (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
This study aims to determine: 1. The effect of numerical intelligence and spatial intelligence on students' mathematical abilities 2. The effect of numerical intelligence on students' mathematical abilities, 3. The effect of spatial intelligence on students' mathematical abilities. The research method used is a survey method with quantitative research on class X IPA Senior High School students of Depok City. The sampling technique was a simple random sampling of 120 samples. The data collection technique was given a test of 20 numerical intelligence items and 20 spatial intelligence items in the form of multiple-choice, while the mathematical ability data were taken from a 15 item test in the form of an essay. Before conducting the hypothesis test, the item validity test for the numerical intelligence test, the spatial intelligence test, and the mathematical ability test were carried out using simple regression correlation. The data normality calculations using the chi-square are declared normal—statistical hypothesis testing with t-test and F test. The results of the study concluded that: 1. There is a significant influence between numerical intelligence and spatial intelligence on the mathematical abilities of students Senior High School students of Depok City, namely f count> f table = 21.81> 3.07; 2. There is a significant effect of numerical intelligence on the mathematical abilities of Depok City Senior High School students, namely t count> t table = 10.00> 1.98; 3. There is a significant effect of spatial intelligence on the mathematical abilities of Depok City Senior High School students, namely t count> t table = 14.80> 1.98